Formulations and Nutrition Value of New Multicomponent Fruit and Berry Liqueurs - Guseinova B.; Ashurbekova F.; Daudova T. (Техника и технология пищевых производств)
Local vegetable raw materials have good prospects in developing new balanced foods with high nutrition value. As a rule, local vegetable raw materials are environmentally friendly and contain a wide range of biologically and physiologically active agents. Fruit liqueurs possess a balanced chemical composition and a high nutrition and physiological value. They produce a recreational or preventive effect on human organism. However, the level of consumption of fresh fruit and berries remains low because of their seasonality. Moreover, the range of fruit and berry products is usually very poor, and very few of them are beneficial for human health and can prevent diseases. The research featured the formulations and production technology for new multicomponent fruit liqueurs of high nutrition value. The liqueurs were made from Dagestan garden and wild fruit and berries with a high content of macro- and micronutrients. The nutrition value and quality of the liqueurs were estimated according to the mass concentration of sugars, titrable acids, vitamins C and P, β-carotene, mineral elements, and phenolic and pectinaceous substances. The sensory properties were measured according to a 10-score system. The paper introduces formulations and technologies for three types of liqueur (Zhivitel’naya, Garmoniya, and Uslada). They involved alcoholized and fermentation-alcoholized juices of grapes, fruit and berry fruit drinks and extracts that mutually complemented each other according to valuable components. The new liqueurs have a high nutrition since 100 cm3 of the liqueur per day partially satisfies the daily requirements for some nutrients: phenolic substances – for 37.5–55.0%; pectinaceous substances – 17.5–32.5%; in vitamin C – 13.7–38.7%, β-carotene – 17.6–43.0%, and a microelement iron – for 14.0–26.0%. The multicomponent fruit liqueurs possess a wide range of biologically and physiologically active agents. As a result, they improve physical activity and increase resistance to bad ecological environment.